PROACTIVE PROCUREMENT PRACTICES IN INDUSTRIES FOR SERVICES PRODUCTS - Kazmi, Syeda Asiya Zenab (My University, 2011)
Today’s modern world’s swift progression in the field of technology, paved way for the creation of innovative products and service offerings for the customers, by the business sector. This very fact boosted the implementation of the phenomenon of corporate “networking” and “outsourcing” through complex and global supply chains for the support, survival and over all corporate success of the industrial sector. Since, the services as being intangible phenomena, attach with its-self great risks (i.e., Financial and reputational) at their procurement level, due to misconceptions, while ordering. Therefore, the modern day’s industrial supply chains are developed, keeping in view, the implementation of the best and successful risk managed proactive procurement practices, to gain the “Competitive Edge”. The aim of my current research effort was to delve into the current industrial practices and trends of “service procurement”, by the manufacturing companies, with reference to the risk management aspect. Hence, the subject research effort has revealed that the current day service procurement practices adopted by the medium sized manufacturing concerns are not properly risk managed & well supported by the smart and innovative tools like lean thinking, as revealed by my current study on the basis of three medium sized sample manufacturing companies (i.e, referred as Company A, B & C). The study results displayed the fact that there is still long way ahead to adopt and implement the best and risk proof practices, like lean thinking as well as the creation of innovative tools and methods, on the basis of risk management principles, by the industrial manufacturing companies, for the overall success and taking the Competitive edge in the manufacturing business field.
Keywords: Competitive edge; networking and outsourcing; proactive procurement; supply chain; lean thinking; innovative tools methods.; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|